World boundaries : (Routledge, 1994)
This set compiles all five volumes of the World Boundaries series: Volume 1: Global Boundaries Volume 2: Middle East and North Africa Volume 3: Eurasia Volume 4: The Americas Volume 5: Maritime Bound Each volume is available separately.